Implementasi Inovasi Media Digital Untuk Meningkatkan Kualitas Pembelajaran Matematika SD Di Gugus Suntalangu - junaidi, junaidi; Sripatmi, Sripatmi; Amrullah, Amrullah; Turmuzi, Muhammad; Hayati, Laila; Hendi, Muhammad (Pendidikan Matematika, FKIP Universitas Mataram, 2025)
The learning process of elementary schools in Suntalangu village has not fully integrated digital technology in the learning process, so innovative technology-based learning has not run optimally. Some of the reasons for this are that schools do not have libraries and laboratories, so students and teachers have limited access to adequate learning resources. Based on this, to improve the quality of mathematics learning in Elementary Schools (SD) Gugus Suntalangu can be done using website-based digital media. Specifically, this media is expected to help visualize the material, increase student interaction, and improve understanding of concepts. Another goal is to improve teachers' ability to integrate digital technology into the learning process and implement innovative digital-based learning approaches. The method of implementation is by holding technology adaptation training for teachers in the suntalangu cluster. The service activity was held at SDN 4 Suntalangu, East Lombok, on May 28, 2025, with 20 teachers from 14 elementary schools as participants. This service has succeeded in improving teachers' ability to use website-based digital media. This learning media has proven to be relevant and effective in helping teachers and students in elementary schools.